2009
DOI: 10.1007/s00421-009-1152-0
|View full text |Cite
|
Sign up to set email alerts
|

The cross-sectional relationships among hyperthermia-induced hyperventilation, peak oxygen consumption, and the cutaneous vasodilatory response during exercise

Abstract: To test the hypothesis that the hyperthermia-induced ventilatory response relates to aerobic power and/or the cutaneous vasodilatory response during exercise, we asked 18 subjects to perform 3 kinds of exercise: an incremental exercise to determine peak oxygen consumption (V(O)(2peak)), a steady state exercise at 50% of V(O)(2peak) to determine the ventilatory response to increasing body temperature, and a steady state exercise at 60% of V(O)(2peak) to determine the cutaneous vasodilatory response to increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
2
20
1
Order By: Relevance
“…When we examined relationships among the ventilatory sensitivity to increasing body temperature, V ・ O2peak and the cutaneous vasodilatory response, we found that ventilatory sensitivity to increasing body temperature has a significant negative relationship with V ・ O2peak and the sensitivity of cutaneous vasodilatory response (Fig. 3) 13) , which is consistent with the compensation hypothesis. On the other hand, Fujii et al 31) recently examined the effect of voluntary hypocapnic hyperventilation on heat-dissipating responses and reported that hypocapnia increases the Tes threshold for cutaneous vasodilation and reduces the sensitivity of the cutaneous vasodilatory response.…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationsupporting
confidence: 73%
“…When we examined relationships among the ventilatory sensitivity to increasing body temperature, V ・ O2peak and the cutaneous vasodilatory response, we found that ventilatory sensitivity to increasing body temperature has a significant negative relationship with V ・ O2peak and the sensitivity of cutaneous vasodilatory response (Fig. 3) 13) , which is consistent with the compensation hypothesis. On the other hand, Fujii et al 31) recently examined the effect of voluntary hypocapnic hyperventilation on heat-dissipating responses and reported that hypocapnia increases the Tes threshold for cutaneous vasodilation and reduces the sensitivity of the cutaneous vasodilatory response.…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationsupporting
confidence: 73%
“…We therefore suggest that hyperthermia-induced hyperventilation is augmented when thermoregulatory responses are impaired during passive heating at rest (hyperthermia-induced hyperventilation is linked to thermoregulatory responses). Consistent with this idea, Hayashi et al (2009) recently showed that during submaximal, moderate intensity exercise in a hot environment, the extent of hyperthermia-induced hyperventilation is inversely related to the thermoregulatory response (cutaneous vasodilation)-i.e., individuals who have a stronger cutaneous vasodilatory response show less hyperthermia-induced hyperventilation. Although this result was from a crosssectional analysis, it suggests that when thermoregulatory responses are enhanced by heat acclimation, hyperthermiainduced hyperventilation during submaximal, moderateintensity exercise may be attenuated.…”
Section: Introductionmentioning
confidence: 76%
“…Our results suggest that EHA reduces ventilation during exercise in a hot environment ( _ V E was reduced by 2.2-3.7 l min -1 ). It is known that hyperthermia stimulates ventilation in resting (Cabanac and White 1995;Fujii et al 2008b) and exercising humans (Beaudin et al 2009;Fujii et al 2008a, b;Hayashi et al 2006Hayashi et al , 2009Nybo and Nielsen 2001). Because exercising T es was significantly reduced by EHA, the reduction in exercise T es can be related to the lower exercise _ V E without changing the slope relating _ V E to T es (see below for detailed ''Discussion'').…”
Section: Co2mentioning
confidence: 94%
See 1 more Smart Citation
“…Nonetheless, it is possible that hyperthermia-induced hyperventilation has some connection to heat-dissipating responses. It has been reported, for example, that ventilatory sensitivity to increasing body temperature (slope of the regression line relating V ・ E to Tes) has a negative linear relationship with the sensitivity of cutaneous vasodilation in heated exercising humans 23) . It has also been reported that subjects with congenital anhidrotic ectodermal dysplasia and those with spinal-cord injuries, leading to reduced sweating responses, show greater increases in ventilation during hyperthermia at rest than healthy subjects 24,25) .…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 99%